2022
DOI: 10.1038/s41467-022-29583-z
|View full text |Cite
|
Sign up to set email alerts
|

Angular and linear speed cells in the parahippocampal circuits

Abstract: An essential role of the hippocampal region is to integrate information to compute and update representations. How this transpires is highly debated. Many theories hinge on the integration of self-motion signals and the existence of continuous attractor networks (CAN). CAN models hypothesise that neurons coding for navigational correlates – such as position and direction – receive inputs from cells conjunctively coding for position, direction, and self-motion. As yet, very little data exist on such conjunctive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 79 publications
2
14
0
Order By: Relevance
“…Consistent with a recent report (Spalla et al, 2022), we also found that a small proportion of HD cells in each of the parahippocampal areas was modulated by linear velocity (speed), although the proportions were smaller than those reported by Spalla et al In contrast, an even larger proportion of ADN HD cells was modulated by linear velocity (Figure 4). When firing rate versus linear velocity tuning curves were constructed for samples that fell within ±60° of the cell's PFD, the percentage of cells that had linear velocity correlations ≥0.7 (accounting for approximately half of the firing rate variance) and absolute values of slopes ≥0.1 cm/s were PoS: 12.6%, PaS: 4.5%, MEC: 12.1%, POR: 10.0%, and ADN: 33.6%.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with a recent report (Spalla et al, 2022), we also found that a small proportion of HD cells in each of the parahippocampal areas was modulated by linear velocity (speed), although the proportions were smaller than those reported by Spalla et al In contrast, an even larger proportion of ADN HD cells was modulated by linear velocity (Figure 4). When firing rate versus linear velocity tuning curves were constructed for samples that fell within ±60° of the cell's PFD, the percentage of cells that had linear velocity correlations ≥0.7 (accounting for approximately half of the firing rate variance) and absolute values of slopes ≥0.1 cm/s were PoS: 12.6%, PaS: 4.5%, MEC: 12.1%, POR: 10.0%, and ADN: 33.6%.…”
Section: Resultssupporting
confidence: 92%
“…Although there are differences in the proportion of cells that encode position, head direction and speed between MEC, PrS and PaS (e.g. PrS and PaS have higher proportions of head-direction tuned cells), these regions share a common substrate of spatial/navigational coding (position, head-direction, speed) [6, 15, 16]. We further found a relationship between navigation variables after clustering that revealed an axis of separation along the head-direction and speed coefficients, such that these variables were negatively related.…”
Section: Discussionmentioning
confidence: 99%
“…Both the MEC and PaS contain large populations of neurons that encode navigationally relevant variables for computing an animals spatial position, including: body position, head direction and running speed. Individual MEC neurons often exhibit a mixture in their selectivity for encoding these variables and, while ∼50 % of MEC neurons can be classified based on metrics that quantify the firing rate profile along a behavioral dimension (tuning curves), a larger proportion of neurons can be classified using more unbiased statistical approaches [13][14][15]. In the PaS, ∼50 % of neurons code for heading direction [6,16], with coding for position or running speed present in about ∼40% neurons [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted March 31, 2023. ; https://doi.org/10.1101/2023.03.29.534808 doi: bioRxiv preprint 33 Keshavarzi et al, 2022;Spalla et al, 2022). Whether the AHV signal is conveyed to each of these areas via the NPH or SGN, or alternatively via other brainstem areas, awaits further investigation.…”
Section: Comparison To Other Studies In Non-human Primates or Immobil...mentioning
confidence: 99%